Brief intervention applied to college students screened positive for at-risk alcohol consumption - Sawicki, Wanda Cristina; Fram, Dayana Souza; Belasco, Angélica Gonçalves Silva (SMAD Revista Eletrônica Saúde Mental Álcool e Drogas (Edição em Português), 2018)
Objective: to investigate the alcohol consumption among nursing college students and evaluate a brief intervention for abusers of alcoholic beverages. Method: longitudinal, experimental study. Data obtained through a self-applicable questionnaire and three instruments. Descriptive statistical analysis and use of specific tests. Results: 36 college students participated in this study. The most used drugs were: alcohol (vodka, beer), tobacco and marijuana. Age of first contact with alcoholic beverages: 15 years; repercussions after use: falls, headache, vomiting and amnesia; and the reasons for consumption: socialization, sensation and pleasure. The brief intervention significantly decreased the risk of consumption among those who abused alcoholic beverages. Among low-risk alcohol consumers, half of them said they were ready to reduce consumption. Conclusion: the short intervention significantly decreased the pattern of alcohol consumption thus promoting the health of the students.